Infrared Solution‐Processed Quantum Dot Solar Cells Reaching External Quantum Efficiency of 80% at 1.35 µm and Jsc in Excess of 34 mA cm−2. Issue 7 (8th January 2018) - Bi, Yu; Pradhan, Santanu; Gupta, Shuchi; Akgul, Mehmet Zafer; Stavrinadis, Alexandros; Konstantatos, Gerasimos
Abstract: Developing low‐cost photovoltaic absorbers that can harvest the short‐wave infrared (SWIR) part of the solar spectrum, which remains unharnessed by current Si‐based and perovskite photovoltaic technologies, is a prerequisite for making high‐efficiency, low‐cost tandem solar cells. Here, infrared PbS colloidal quantum dot (CQD) solar cells employing a hybrid inorganic–organic ligand exchange process that results in an external quantum efficiency of 80% at 1.35 µm are reported, leading to a short‐circuit current density of 34 mA cm −2 and a power conversion efficiency (PCE) up to 7.9%, which is a current record for SWIR CQD solar cells. When this cell is placed at the back of an MAPbI3 perovskite film, it delivers an extra 3.3% PCE by harnessing light beyond 750 nm. Abstract : PbS colloidal quantum dot solar cells with high quantum efficiency (EQE) in the infrared are reported as a result of optimized surface passivation, band alignment, and optical design. The reported solar cells achieve short‐circuit current density over 34 mA cm −2, external quantum efficiency (EQE) of 80% at 1350 nm, and power conversion efficiency of 7.9% under one sun illumination.